Survei Kondisi Fisik Atlet Joyoboyo Taekwondo Club (JTC) Kabupaten Kediri Usia Junior 15-17 Tahun - Firda Fitriana; Eko Hariyanto (Jayabama: Jurnal Peminat Olahraga, 2024)
The aim of this study was to find out the physical condition of Joyoboyo Taekwondo Club (JTC) Kediri Regency junior athletes aged 15-17 years. The method used is a survey with data collection techniques using tests and measurements. The population in this study were Joyoboyo Taekwondo Club (JTC) Kediri Regency athletes aged 15-17 years, totaling 18 athletes, with details of 12 male athletes and 6 female athletes, who were taken using total sampling techniques. In this study, the instruments used were test instruments in the form of strength tests (sit ups), endurance (balke), flexibility (sit and reach dynamometer), agility (T test), balance (standing stork test), speed (30 meter run) , explosive power in the leg muscles (standing broad jump). The data that has been obtained is then analyzed using quantitative descriptive analysis techniques. The results of this study show that the results of the abdominal muscle strength test (sit ups) for male and female athletes are predominantly in the "average" category. The results of the endurance test (balke) for male and female athletes are predominantly in the "very poor" category. For the results of the flexibility test (sit and reach dynamometer), male and female athletes are predominantly in the "very good" category. For the results of the agility test (T test), male and female athletes are predominantly in the "poor" category, for the results of the balance test (standing stork test) are predominantly in the "bad" category, for the results of the speed test (30 meter run) male and female athletes dominantly in the "very poor" category and for the results of the leg muscle explosive power test (standing broad jump) male and female athletes are predominantly in the "above average" category.